A graphene alloy composite material and its preparation method and application
A graphene alloy composite material is prepared through expansion, acidification, and reduction processes, enhancing dispersibility and electromagnetic shielding performance in water-based coatings, addressing the limitations of existing graphene-based materials.
Patent Information
- Application Number
- CN202111057651.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-09
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2041-09-09
AI Technical Summary
Graphene has poor dispersibility in water-based coatings, leading to poor electromagnetic shielding performance and affecting the coating's effectiveness, and existing graphene-based electromagnetic shielding materials have limited spectrum range and poor dispersibility.
A method involving expandable graphite expansion, acidification, ultrasonic exfoliation, and reduction reactions with silver-cerium modification, followed by addition of tetrahydroxyphenylporphyrin nanorods and urea in phosphoric acid, to create a graphene alloy composite material with improved dispersibility and wide electromagnetic shielding spectrum.
The composite material achieves excellent electromagnetic shielding in a wide spectrum range with good dispersibility in water-based coatings, suitable for large-scale applications.
Smart Images

Figure BDA0003255329450000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of graphene new material applications, and in particular to a graphene alloy composite material and a preparation method and application thereof. Background Art
[0002] Paint is a very important decorative material in today's society, which can beautify and protect. Traditional paint will release a large amount of carcinogenic organic compounds (VOC) during the volatilization process, polluting the environment and affecting human health. Water-based paint is an organic polymer paint with water as the dispersion medium. After coating, the water gradually evaporates to form an organic polymer coating. Therefore, water-based paint is an environmentally friendly paint product and is widely used in various fields.
[0003] Among them, water-based coatings with electromagnetic shielding effects are very important in the fields of electronic components, circuit board printing, construction, military, aerospace, etc. They can guide electric current and eliminate the ability to accumulate static charges. On the one hand, they can prevent electromagnetic radiation in the environment from interfering with the signals of electronic products, making the signals of electronic products fidelity and stable; on the other hand, they can prevent electronic products from polluting the environment with electromagnetic radiation, making the signals of electronic products confidential.
[0004] Graphene is a carbon atom with sp 2 The hybrid orbitals are arranged in a honeycomb lattice to form a single-layer two-dimensional crystal. Its excellent electrical conductivity makes it very promising in the field of electromagnetic shielding. However, graphene has very poor dispersibility in water. It is difficult to exert the electromagnetic shielding performance of graphene by directly adding it to water-based coatings, and it will also affect the coating effect of water-based coatings.
[0005] Patent CN108135119B discloses an electromagnetic shielding material based on porous graphene-alloy silicon, including porous graphene, nano-scale alloy silicon filled in the pores of the porous graphene, and alloy silicon attached to the surface of the porous graphene. The amount of this electromagnetic shielding material used in the preparation of the coating is relatively large, but its dispersibility in the coating is poor, which seriously affects the performance of the coating. In addition, its electromagnetic shielding effect on low-frequency and high-frequency electromagnetic shielding is also poor, and the electromagnetic shielding spectrum range is small. Summary of the invention
[0006] The purpose of the present invention is to provide a graphene alloy composite material and a preparation method thereof, which has a wide electromagnetic shielding spectrum range and good electromagnetic shielding effect.
[0007] To achieve the above object, the present invention is implemented by the following scheme:
[0008] A method for preparing a graphene alloy composite material, the specific steps are as follows:
[0009] (1) Using expandable graphite as a raw material, subjecting it to expansion treatment and acidification and ultrasonic exfoliation to obtain graphene;
[0010] (2) dispersing the graphene obtained in step (1) in water by ultrasonic wave, maintaining ultrasonic oscillation, adding silver ammonia solution, cerium nitrate solution and hydrazine hydrate solution, and performing reduction reaction to obtain a silver-cerium modified graphene composite material;
[0011] (3) adding the silver-cerium modified graphene composite material obtained in step (2) to the aqueous dispersion of tetrahydroxyphenylporphyrin nanorods, and uniformly dispersing by ultrasonication to obtain a pre-dispersion liquid;
[0012] (4) adding urea to the phosphoric acid aqueous solution, stirring and mixing, and then adding the pre-dispersed liquid obtained in step (3), and subjecting to heat treatment, to obtain the graphene alloy composite material.
[0013] Preferably, in parts by weight, the specific method of step (1) is as follows: first, 1 part of expandable graphite is subjected to microwave treatment to obtain expanded graphite, then the expanded graphite is added to 5 to 7 parts of 65 to 75% by volume ethanol aqueous solution, ultrasonically treated for the first time, centrifuged, and dried to obtain pretreated graphite, and then the pretreated graphite is added to 4 to 6 parts of a strong acid solution, ultrasonically treated for the second time, centrifuged, washed, and dried to obtain graphene.
[0014] Further preferably, the process conditions of the microwave treatment are: 10-12 kW microwave treatment for 25-35 s.
[0015] More preferably, the process conditions for the first ultrasonic treatment are: 300-400W ultrasonic oscillation for 20-30 minutes; and the process conditions for the second ultrasonic treatment are: 500-600W ultrasonic oscillation for 45-55 minutes.
[0016] Further preferably, the strong acid solution is obtained by mixing concentrated nitric acid (mass concentration 98%) and concentrated sulfuric acid (mass concentration 98%) in a volume ratio of 1:3.
[0017] Preferably, in parts by weight, the specific method of step (2) is as follows: first, 1 part of graphene is added to 20-30 parts of water, and ultrasonic oscillation is performed at 300-400W for 20-30 minutes, followed by adding 0.4-0.6 parts of silver ammonia solution, 0.2-0.3 parts of cerium nitrate solution with a mass concentration of 20-30% and 4-6 parts of hydrazine hydrate solution with a mass concentration of 12-15%, stirring for reduction reaction, and centrifuging to obtain the precipitate to obtain the silver-cerium modified graphene composite material.
[0018] Further preferably, the process conditions of the stirring reduction reaction are: 800-1000 r / min and 40-50° C., and stirring the reaction for 80-100 minutes.
[0019] Preferably, in step (2), the preparation method of the silver ammonia solution is as follows, in parts by weight: first, add 1 part of silver nitrate to 10 parts of pure water, stir until completely dissolved, then add 5 parts of 30% ammonia solution by mass, stir until completely clear and transparent, to obtain the silver ammonia solution.
[0020] Preferably, in step (3), the preparation method of the pre-dispersion liquid is as follows, in parts by weight: first, 1 part of the silver-cerium modified graphene composite material is added to 3-4 parts of the tetrahydroxyphenylporphyrin nanorod aqueous dispersion liquid, and ultrasonically dispersed uniformly to obtain the pre-dispersion liquid; wherein the tetrahydroxyphenylporphyrin nanorod aqueous dispersion liquid is obtained by adding 1 part by weight of the tetrahydroxyphenylporphyrin nanorods to 4-6 parts by weight of water, and ultrasonically dispersing uniformly.
[0021] Further preferably, in parts by weight, the preparation method of tetrahydroxyphenylporphyrin nanorods is as follows: first, add 1 part of tetrahydroxyphenylporphyrin to 5-7 parts of 0.1-0.2 mol / L sodium hydroxide solution to obtain an alkaline dispersion; then add 1-2 mol / L hydrochloric acid solution to 10-12 parts of 2-3 mmol / L hexadecyltrimethylammonium bromide aqueous solution, then add the alkaline dispersion, adjust the pH to 2-3, stir at room temperature for 45-50 hours, and centrifuge to obtain.
[0022] Preferably, in parts by weight, the specific method of step (4) is as follows: first, add 1 part of urea to 1.2-1.5 parts of a phosphoric acid solution preheated to 70-80° C. and having a mass concentration of 70-80%, stir and heat to 110-120° C., add 1-1.5 parts of the pre-dispersion liquid, continue to heat to 130-140° C., keep warm for 20-30 minutes, spray dry to obtain a powder, and finally heat the powder at 190-200° C. for 80-100 minutes to obtain the graphene alloy composite material.
[0023] The present invention also claims protection for a graphene alloy composite material obtained by the above-mentioned preparation method and the use of the above-mentioned graphene alloy composite material in the preparation of electromagnetic shielding water-based coatings.
[0024] The present invention also protects an electromagnetic shielding water-based coating, comprising the above-mentioned graphene alloy composite material.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The present invention first uses expandable graphite as a raw material, and obtains graphene through expansion treatment and acidification ultrasonic peeling; then the graphene is ultrasonically dispersed in water, and ultrasonic oscillation is maintained, and silver ammonia solution, cerium nitrate solution and hydrazine hydrate solution are added to perform a reduction reaction to obtain a silver-cerium modified graphene composite material; then the silver-cerium modified graphene composite material is added to a tetrahydroxyphenylporphyrin nanorod aqueous dispersion, and ultrasonic dispersion is performed uniformly to obtain a pre-dispersion liquid; finally, urea is added to a phosphoric acid aqueous solution, and after stirring and mixing, the pre-dispersion liquid is added, and heat treatment is performed to obtain a graphene alloy composite material. The composite material has a wide electromagnetic shielding spectrum range, good electromagnetic shielding effect, and good dispersibility in water, and can be used for the production of electromagnetic shielding water-based coatings.
[0027] (2) The present invention disperses graphene in water, maintains ultrasonic oscillation to reduce graphene agglomeration, adds silver ammonia solution and cerium nitrate to carry out reduction reaction, and the generated silver and cerium are deposited on the graphene surface to obtain a silver-cerium modified graphene composite material, which can better improve the electromagnetic shielding performance of the composite material.
[0028] (3) The present invention adds urea to a phosphoric acid aqueous solution, and then adds a pre-dispersion prepared in advance by a silver-cerium modified graphene composite material and a tetrahydroxyphenylporphyrin nanorod aqueous dispersion, performs heat treatment, generates ammonium polyphosphate on the surface, and assembles porphyrin nanorods. The ammonium polyphosphate has a low degree of polymerization and contains hydrophilic groups such as ammonium ions. The porphyrin nanorods also contain hydrophilic groups such as hydroxyls, which greatly improves the hydrophilicity of the composite material. The composite material can be evenly dispersed in water and used in the production of water-based coatings. The water-based coating has an excellent electromagnetic shielding effect and is suitable for large-scale applications. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] A method for preparing a graphene alloy composite material, the specific steps are as follows:
[0032] (1) first subjecting 1 g of expandable graphite to a 12 kW microwave treatment for 25 s to obtain expanded graphite, then adding the expanded graphite to 5 g of a 75% ethanol aqueous solution, oscillating ultrasonically at 400 W for 20 minutes, centrifuging, and drying to obtain pretreated graphite, then adding the pretreated graphite to 4 g of a strong acid solution, oscillating ultrasonically at 600 W for 45 minutes, centrifuging, washing, and drying to obtain graphene;
[0033] (2) adding 1 g of graphene to 30 g of water, oscillating with 300 W ultrasonic waves for 30 minutes, then adding 0.4 g of silver ammonia solution, 0.2 g of 30% cerium nitrate solution and 6 g of 12% hydrazine hydrate solution, stirring at 1000 r / min and 40° C. for 100 minutes, and centrifuging to obtain the precipitate to obtain the silver-cerium modified graphene composite material;
[0034] (3) adding 1 g of the silver-cerium modified graphene composite material to 4 g of a tetrahydroxyphenylporphyrin nanorod aqueous dispersion, and dispersing the mixture uniformly by ultrasonication to obtain a pre-dispersion solution; wherein the tetrahydroxyphenylporphyrin nanorod aqueous dispersion solution is prepared by adding 1 g of the tetrahydroxyphenylporphyrin nanorod to 4 g of water, and dispersing the mixture uniformly by ultrasonication to obtain a pre-dispersion solution;
[0035] (4) Add 1 g of urea to 1.2 g of a 70% mass concentration phosphoric acid solution preheated to 80° C., heat to 120° C. with stirring, add 1 g of the pre-dispersion solution, continue to heat to 140° C., keep warm for 20 minutes, spray dry to obtain a powder, and finally heat the powder at 200° C. for 80 minutes to obtain the graphene alloy composite material.
[0036] The strong acid solution is obtained by mixing concentrated nitric acid (mass concentration 98%) and concentrated sulfuric acid (mass concentration 98%) in a volume ratio of 1:3.
[0037] In step (2), the preparation method of the silver ammonia solution is as follows: first, add 1 g of silver nitrate to 10 g of pure water, stir until it is completely dissolved, then add 5 g of 30% ammonia solution, stir until it is completely clear and transparent, and the silver ammonia solution is obtained.
[0038] The preparation method of the tetrahydroxyphenylporphyrin nanorods is as follows: first, 1g of tetrahydroxyphenylporphyrin is added to 7g of 0.1mol / L sodium hydroxide solution to obtain an alkaline dispersion; then, a 2mol / L hydrochloric acid solution is added to 12g of a 2mmol / L hexadecyltrimethylammonium bromide aqueous solution, and then the alkaline dispersion is added, the pH is adjusted to 2, stirred at room temperature for 50 hours, and centrifuged to obtain the nanorods.
[0039] Example 2
[0040] A method for preparing a graphene alloy composite material, the specific steps are as follows:
[0041] (1) first subjecting 1 g of expandable graphite to a 10 kW microwave treatment for 35 s to obtain expanded graphite, then adding the expanded graphite to 7 g of a 65% ethanol aqueous solution, oscillating ultrasonically at 300 W for 30 minutes, centrifuging, and drying to obtain pretreated graphite, then adding the pretreated graphite to 6 g of a strong acid solution, oscillating ultrasonically at 500 W for 55 minutes, centrifuging, washing, and drying to obtain graphene;
[0042] (2) adding 1 g of graphene to 20 g of water, oscillating with ultrasonic waves at 400 W for 20 minutes, then adding 0.6 g of silver ammonia solution, 0.3 g of 20% cerium nitrate solution and 4 g of 15% hydrazine hydrate solution, stirring at 800 r / min and 50° C. for 80 minutes, and centrifuging to obtain the precipitate to obtain the silver-cerium modified graphene composite material;
[0043] (3) adding 1 g of the silver-cerium modified graphene composite material to 3 g of a tetrahydroxyphenylporphyrin nanorod aqueous dispersion, and uniformly dispersing the mixture by ultrasonication to obtain a pre-dispersion solution; wherein the tetrahydroxyphenylporphyrin nanorod aqueous dispersion solution is prepared by adding 1 g of the tetrahydroxyphenylporphyrin nanorod to 6 g of water, and uniformly dispersing the mixture by ultrasonication to obtain a pre-dispersion solution;
[0044] (4) Add 1 g of urea to 1.5 g of a phosphoric acid solution preheated to 70° C. with a mass concentration of 80%, stir and heat to 110° C., add 1.5 g of the pre-dispersion solution, continue to heat to 130° C., keep warm for 30 minutes, spray dry to obtain a powder, and finally heat the powder at 190° C. for 100 minutes to obtain the graphene alloy composite material.
[0045] The strong acid solution is obtained by mixing concentrated nitric acid (mass concentration 98%) and concentrated sulfuric acid (mass concentration 98%) in a volume ratio of 1:3.
[0046] In step (2), the preparation method of the silver ammonia solution is as follows: first, add 1 g of silver nitrate to 10 g of pure water, stir until it is completely dissolved, then add 5 g of 30% ammonia solution, stir until it is completely clear and transparent, and the silver ammonia solution is obtained.
[0047] The preparation method of the tetrahydroxyphenylporphyrin nanorods is as follows: first, 1g of tetrahydroxyphenylporphyrin is added to 5g of 0.2mol / L sodium hydroxide solution to obtain an alkaline dispersion; then, 1mol / L hydrochloric acid solution is added to 10g of 3mmol / L hexadecyltrimethylammonium bromide aqueous solution, and then the alkaline dispersion is added, the pH is adjusted to 3, stirred at room temperature for 45 hours, and centrifuged to obtain the nanorods.
[0048] Example 3
[0049] A method for preparing a graphene alloy composite material, the specific steps are as follows:
[0050] (1) 1 g of expandable graphite was subjected to 11 kW microwave treatment for 30 s to obtain expanded graphite, and then the expanded graphite was added to 6 g of 70% ethanol aqueous solution by volume, 400 W ultrasonic oscillation was performed for 25 minutes, centrifuged, and dried to obtain pretreated graphite, and then the pretreated graphite was added to 5 g of strong acid solution, 600 W ultrasonic oscillation was performed for 50 minutes, centrifuged, washed, and dried to obtain graphene;
[0051] (2) adding 1 g of graphene to 25 g of water, oscillating with ultrasonic waves at 400 W for 25 minutes, then adding 0.5 g of silver ammonia solution, 0.25 g of 25% cerium nitrate solution and 5 g of 13% hydrazine hydrate solution, stirring at 900 r / min and 45° C. for 90 minutes, and centrifuging to obtain the precipitate to obtain the silver-cerium modified graphene composite material;
[0052] (3) adding 1 g of the silver-cerium modified graphene composite material to 3.5 g of a tetrahydroxyphenylporphyrin nanorod aqueous dispersion, and dispersing the mixture uniformly by ultrasonication to obtain a pre-dispersion solution; wherein the tetrahydroxyphenylporphyrin nanorod aqueous dispersion solution is prepared by adding 1 g of the tetrahydroxyphenylporphyrin nanorod to 5 g of water, and dispersing the mixture uniformly by ultrasonication to obtain a pre-dispersion solution;
[0053] (4) Add 1 g of urea to 1.3 g of a 75% mass concentration phosphoric acid solution preheated to 75° C., heat to 115° C. with stirring, add 1.2 g of the pre-dispersion solution, continue to heat to 135° C., keep warm for 25 minutes, spray dry to obtain a powder, and finally heat the powder at 195° C. for 90 minutes to obtain the graphene alloy composite material.
[0054] The strong acid solution is obtained by mixing concentrated nitric acid (mass concentration 98%) and concentrated sulfuric acid (mass concentration 98%) in a volume ratio of 1:3.
[0055] In step (2), the preparation method of the silver ammonia solution is as follows: first, add 1 g of silver nitrate to 10 g of pure water, stir until it is completely dissolved, then add 5 g of 30% ammonia solution, stir until it is completely clear and transparent, and the silver ammonia solution is obtained.
[0056] The preparation method of the tetrahydroxyphenylporphyrin nanorods is as follows: first, 1g of tetrahydroxyphenylporphyrin is added to 6g of 0.15mol / L sodium hydroxide solution to obtain an alkaline dispersion; then, 1.5mol / L hydrochloric acid solution is added to 11g of 2.5mmol / L hexadecyltrimethylammonium bromide aqueous solution, and then the alkaline dispersion is added, the pH is adjusted to 3, stirred at room temperature for 48 hours, and centrifuged to obtain the nanorods.
[0057] Comparative Example 1
[0058] A method for preparing a graphene alloy composite material, the specific steps are as follows:
[0059] (1) 1 g of expandable graphite was subjected to 12 kW microwave treatment for 25 s to obtain expanded graphite, and then the expanded graphite was added to 5 g of 75% ethanol aqueous solution by volume, 400 W ultrasonic oscillation was performed for 20 minutes, centrifuged, and dried to obtain pretreated graphite, and then the pretreated graphite was added to 4 g of strong acid solution, 600 W ultrasonic oscillation was performed for 45 minutes, centrifuged, washed, and dried to obtain graphene;
[0060] (2) adding 1 g of graphene to 30 g of water, oscillating with 300 W ultrasonic waves for 30 minutes, then adding 0.4 g of silver ammonia solution and 6 g of 12% hydrazine hydrate solution, stirring and reacting for 100 minutes at 1000 r / min and 40° C., and centrifuging to obtain the precipitate to obtain the silver-cerium modified graphene composite material;
[0061] (3) Add 1 g of urea to 1.2 g of a 70% mass concentration phosphoric acid solution preheated to 80° C., stir and heat to 120° C., add 0.2 g of a silver-cerium modified graphene composite material, continue to heat to 140° C., keep warm for 20 minutes, spray dry to obtain a powder, and finally heat the powder at 200° C. for 80 minutes to obtain the graphene alloy composite material.
[0062] The strong acid solution is obtained by mixing concentrated nitric acid (mass concentration 98%) and concentrated sulfuric acid (mass concentration 98%) in a volume ratio of 1:3.
[0063] In step (2), the preparation method of the silver ammonia solution is as follows: first, add 1 g of silver nitrate to 10 g of pure water, stir until it is completely dissolved, then add 5 g of 30% ammonia solution, stir until it is completely clear and transparent, and the silver ammonia solution is obtained.
[0064] Comparative Example 2
[0065] A method for preparing a graphene alloy composite material, the specific steps are as follows:
[0066] (1) 1 g of expandable graphite was subjected to 12 kW microwave treatment for 25 s to obtain expanded graphite, and then the expanded graphite was added to 5 g of 75% ethanol aqueous solution by volume, 400 W ultrasonic oscillation was performed for 20 minutes, centrifuged, and dried to obtain pretreated graphite, and then the pretreated graphite was added to 4 g of strong acid solution, 600 W ultrasonic oscillation was performed for 45 minutes, centrifuged, washed, and dried to obtain graphene;
[0067] (2) adding 1 g of graphene to 30 g of water, oscillating with 300 W ultrasonic waves for 30 minutes, then adding 0.4 g of silver ammonia solution and 6 g of 12% hydrazine hydrate solution, stirring and reacting for 100 minutes at 1000 r / min and 40° C., and centrifuging to obtain the precipitate to obtain the silver-cerium modified graphene composite material;
[0068] (3) adding 1 g of the silver-cerium modified graphene composite material to 4 g of a tetrahydroxyphenylporphyrin nanorod aqueous dispersion, and uniformly dispersing the mixture by ultrasonication to obtain a pre-dispersion; wherein the tetrahydroxyphenylporphyrin nanorod aqueous dispersion is prepared by adding 1 g of the tetrahydroxyphenylporphyrin nanorod to 4 g of water, uniformly dispersing the mixture by ultrasonication to obtain a pre-dispersion, stirring the mixture at 140° C. for 20 minutes, spray drying the mixture, and finally heat treating the powder at 200° C. for 80 minutes to obtain the graphene alloy composite material.
[0069] The strong acid solution is obtained by mixing concentrated nitric acid (mass concentration 98%) and concentrated sulfuric acid (mass concentration 98%) in a volume ratio of 1:3.
[0070] In step (2), the preparation method of the silver ammonia solution is as follows: first, add 1 g of silver nitrate to 10 g of pure water, stir until it is completely dissolved, then add 5 g of 30% ammonia solution, stir until it is completely clear and transparent, and the silver ammonia solution is obtained.
[0071] The preparation method of the tetrahydroxyphenylporphyrin nanorods is as follows: first, 1g of tetrahydroxyphenylporphyrin is added to 7g of 0.1mol / L sodium hydroxide solution to obtain an alkaline dispersion; then, a 2mol / L hydrochloric acid solution is added to 12g of a 2mmol / L hexadecyltrimethylammonium bromide aqueous solution, and then the alkaline dispersion is added, the pH is adjusted to 2, stirred at room temperature for 50 hours, and centrifuged to obtain the nanorods.
[0072] The performance of the materials prepared in Examples 1-3 and Comparative Examples 1-2 was evaluated:
[0073] Take 1g of the composite materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2, respectively, and put them into a four-necked bottle containing 60g of water together with 2g of emulsifier OP-10 and 0.8g of sodium dodecylbenzene sulfonate, and stir and mix them with a stirrer; put a monomer mixture consisting of 20g of acrylic acid and 30g of n-butyl acrylate into a constant pressure dropping funnel, and drip it into the four-necked bottle from the upper end of the reflux condenser, and accelerate the stirring, and control the temperature to be kept at 78°C; then add 0.3g of ammonium persulfate, and then dissolve 8g of sodium p-styrene sulfonate as a copolymerization modified monomer in a small amount of distilled water and add it in batches; after the dripping is completed, keep warm and stir for 2 hours, and adjust the value to 8 with ammonia water to obtain the coating. The coating is applied to the surface of the polycarbonate sheet, and the drying time is 2 hours, and the coating thickness is 100μm.
[0074] Refer to GJB 6190-2008 "Measurement Method of Shielding Effectiveness of Electromagnetic Shielding Materials" to investigate the electromagnetic shielding effect;
[0075] The coating bonding strength was tested using an XH-M coating bonding strength tester (Beijing Tiandi Xinghuo Technology Development Co., Ltd.).
[0076] The test results are shown in Table 1.
[0077] Table 1. Coating performance investigation
[0078]
[0079] It can be seen from Table 1 that the water-based coatings made of the composite materials obtained in Examples 1 to 3 have high bonding strength, good coating performance, high shielding effectiveness in the frequency range of 10kHz-40GHz, a wide electromagnetic shielding spectrum range, and good electromagnetic shielding effect, and are all superior to the performance of Comparative Examples 1-2.
[0080] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0081] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a graphene alloy composite material, characterized in that: The specific steps are as follows: (1) Using expandable graphite as a raw material, subjecting it to expansion treatment and acidification and ultrasonic exfoliation to obtain graphene; (2) dispersing the graphene obtained in step (1) in water by ultrasonic wave, maintaining ultrasonic oscillation, adding silver ammonia solution, cerium nitrate solution and hydrazine hydrate solution, and performing reduction reaction to obtain a silver-cerium modified graphene composite material; (3) adding the silver-cerium modified graphene composite material obtained in step (2) to the aqueous dispersion of tetrahydroxyphenylporphyrin nanorods, and uniformly dispersing by ultrasonication to obtain a pre-dispersion liquid; (4) adding urea to the phosphoric acid aqueous solution, stirring and mixing, and then adding the pre-dispersed liquid obtained in step (3), and subjecting to heat treatment, to obtain the graphene alloy composite material.
2. The preparation method according to claim 1, characterized in that: In parts by weight, the specific method of step (1) is as follows: 1 part of expandable graphite is subjected to microwave treatment to obtain expanded graphite, then the expanded graphite is added to 5 to 7 parts of 65 to 75% by volume ethanol aqueous solution, subjected to a first ultrasonic treatment, centrifuged, and dried to obtain pretreated graphite, and then the pretreated graphite is added to 4 to 6 parts of a strong acid solution, subjected to a second ultrasonic treatment, centrifuged, washed, and dried to obtain graphene.
3. The preparation method according to claim 2, characterized in that: The process conditions of microwave treatment are: 10-12 kW microwave treatment for 25-35 s.
4. The preparation method according to claim 2, characterized in that: The process conditions of the first ultrasonic treatment are: 300-400W ultrasonic oscillation for 20-30 minutes; the process conditions of the second ultrasonic treatment are: 500-600W ultrasonic oscillation for 45-55 minutes.
5. The preparation method according to claim 1, characterized in that: In parts by weight, the specific method of step (2) is as follows: first, 1 part of graphene is added to 20-30 parts of water, and ultrasonic oscillation is performed at 300-400W for 20-30 minutes, followed by adding 0.4-0.6 parts of silver ammonia solution, 0.2-0.3 parts of cerium nitrate solution with a mass concentration of 20-30% and 4-6 parts of hydrazine hydrate solution with a mass concentration of 12-15%, stirring for reduction reaction, and centrifuging to obtain a precipitate to obtain the silver-cerium modified graphene composite material.
6. The preparation method according to claim 1, characterized in that: In parts by weight, the specific method of step (4) is as follows: first, add 1 part of urea to 1.2-1.5 parts of a phosphoric acid solution preheated to 70-80° C. and having a mass concentration of 70-80%, stir and heat to 110-120° C., add 1-1.5 parts of the pre-dispersion liquid, continue to heat to 130-140° C., keep warm for 20-30 minutes, spray dry to obtain a powder, and finally heat the powder at 190-200° C. for 80-100 minutes to obtain the graphene alloy composite material.
7. A graphene alloy composite material prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the graphene alloy composite material according to claim 7 in the preparation of electromagnetic shielding water-based coating.
9. An electromagnetic shielding water-based coating, characterized in that: A graphene alloy composite material comprising the graphene alloy composite material according to claim 7.
Citation Information
Patent Citations
An electromagnetic shielding material based on porous graphene-silicon alloy, its preparation method, and coatings.
CN108135119B
Metal / grapheme nanocomposite and preparation method thereof
CN103286308A
Preparation method of silver nanocrystal-multilayer graphene composite material
CN104591174A
Flexible graphene-based composite film, and preparation method and application thereof as electromagnetic shielding material
CN108003364A
Large-area reduced graphene oxide sheet for high thermal conductivity and electromagnetic shielding and method for manufacturing the same
KR101650180B1